2020
DOI: 10.1038/s41598-020-67611-4
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous ZnAl2Si10O24 nanofertilizers enable high yield of Oryza sativa L.

Abstract: Controllable release of nutrients in soil can overcome the environmental problems associated with conventional fertilizer. Here we synthesized mesoporous nanocomposite of Zinc aluminosilicate (ZnAl2Si10O24) via co-precipitation method. Oryza sativa L. husk was used as source of silica for making the synthesis process green and economical. The nanocomposite was subsequently loaded with urea to achieve the demand of simultaneous and slow delivery of both zinc and urea. The structural characterization of nanocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Both surface area and pore distribution are critical for evaluating mesoporous materials; thus, all of the N 2 adsorption-desorption isotherms of Gd 2 O 3 @MSN using BJH (Figures 4A,B) were evaluated. The samples exhibit typical type IV curves with an evident hysteresis loop, confirming its mesoporous nature (López et al, 2006;Liu et al, 2015;Philippart et al, 2017;Francesca et al, 2018;Naseem et al, 2020;Zhou et al, 2020). The BET test results also suggest that the surface area of the MSN was around 822.96 m 2 /g, making them much larger than previous versions of similar compounds (Shao et al, 2011).…”
Section: Discussionsupporting
confidence: 53%
“…Both surface area and pore distribution are critical for evaluating mesoporous materials; thus, all of the N 2 adsorption-desorption isotherms of Gd 2 O 3 @MSN using BJH (Figures 4A,B) were evaluated. The samples exhibit typical type IV curves with an evident hysteresis loop, confirming its mesoporous nature (López et al, 2006;Liu et al, 2015;Philippart et al, 2017;Francesca et al, 2018;Naseem et al, 2020;Zhou et al, 2020). The BET test results also suggest that the surface area of the MSN was around 822.96 m 2 /g, making them much larger than previous versions of similar compounds (Shao et al, 2011).…”
Section: Discussionsupporting
confidence: 53%
“…Results are so far encouraging. For instance, Naseem et al [83] studied the response of Oryza sativa in a pot experiment when fertilized with commercial urea or Si mesoporous nanoparticles (ZnAl 2 Si 10 O 24 ; 64 nm) functionalized with urea; both fertilizers were applied to the soil at the same doses. The authors observed that the release of urea from the nanocomposite was maximum and faster in the first three days and it lasted up to 336 h (14 days).…”
Section: Si Nanoparticles As Plant Nutrient Carriermentioning
confidence: 99%
“…These types of fertilizers can also be prepared by the encapsulation of nutrients within the nanomaterials [31][32][33]. Nano-fertilizers can improve the yield and quality of crops with increased nutrient usage efficiency, while lessening the production cost and thereby resulting in a sustainable agriculture [34][35][36][37][38]. The use of pesticide is a common practice in agriculture and several studies have been carried out for the advancement of effective pesticides [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%